Linguistic Borrowing of English Words and Utterances among Philippine’s Generation Z in Cebuano Visayan - Sales, April Jane G. (REiLA : Journal of Research and Innovation in Language, 2022)
This descriptive-qualitative study investigates the English-borrowed words in the Cebuano Visayan vocabularies uttered by the select Generation Z in the Southern part of Cebu in the Philippines. The validated self-made matrix from 15 live recorded role-plays of the 80 participants involved in this study. It was analysed in 3 phases; Phase one for Code-mixing in words, Phase two for Code-Switching in utterances, and phase three for monograph construction out from the data-gathering procedure of the study. This study is anchored on the phylogenetic change proposed by Hockett (2008) and the Borrowing Transfer Theory by Odlin (1989). These theories magnify that modification of one or both languages may occur whenever two languages come into contact. The phylogenetic change focuses on language switching and mixing in a specific speaking community. The study's findings showed that most Cebuano Visayan affixes occur in words under verbs. The affixes of the Cebuano Visayan language under adjectives do not significantly influence the meaning of the word but function as an auxiliary in the English word mixed in it. The majority of the content words are in complex grammatical form. Among the three types of code-switching, intrasentential codeswitching is mainly applied. Therefore, it is concluded that Cebuano Visayan uses linguistic borrowing from English through code-mixing in words and code-mixing in utterances. Because these phenomena augment genuine knowledge acquisition, it is recommended that Language Teachers allow the students to use more than one code in oral classroom participation through code-mixing and code-switching.